Twosome Coloring: Designing a Playful Coloring System on Dual-sided Transparent Surfaces - Kim, Heesun; Lee, Seung A.; Kim, Hyoyoung; Park, Ji-hyung (PROCEEDINGS OF THE 2016 ACM INTERNATIONAL CONFERENCE ON INTERACTIVE SURFACES AND SPACES, (ISS 2016), 2016)
This paper introduces a coloring application for dual-sided transparent surfaces. It extends the traditional coloring experience with see-through display technology and dual-sided interaction techniques that enable a playful user experience. Twosome Coloring allows two users to interact with a see-through color picker and twosome interaction techniques on dual-sided transparent surfaces. We describe design concerns related to see-through technology, dual-sided interaction and application design, and present the results from a preliminary user study that indicates the benefit of see-through interface and twosome interactions.